Oceanic New York - Mentz, Steve; Mentz, Steve (Brooklyn, NY punctum books, 2015)
This volume comprises a three-fold object, Book and Ocean and New York City. If this Book were Ocean, how would it feel between your fingers? Wet and slippery, just a bit warmer or colder than the air around it, since the Ocean is our planet$1 (Bs greatest reservoir of heat, a sloshing insulator and incubator girdling our globe. If its pages were New York City, how would they abrade your imagination? Human and teeming, endlessly humming along with that same old tune. Imagine that these three things were one thing. All together: Book and Ocean and New York City. During the long historical pause between the day the last sailing ship docked at South Street and that day in October 2012 when Hurricane Sandy brought the waves back in fury, New York turned its back on the sea. This Book remembers that the City was founded on Ocean, peopled by its currents, grew rich on its traffic. The storm taught what we should never have forgotten: under New York$1 (Bs asphalt lies not beach but Ocean.s
English
Keywords: Social impact of environmental issues; oceanic studies; cultural studies; ecology; New York City; environmental humanities